The effective action of D6-branes in N = 1 type IIA orientifolds - Kerstan, Max; Weigand, Timo (Journal of high energy physics, 2011)
We use a Kaluza-Klein reduction to compute the low-energy effective action for the massless modes of a spacetime-filling D6-brane wrapped on a special Lagrangian 3-cycle of a type IIA Calabi-Yau orientifold. The modifications to the characteristic data of the N=1N=1 \mathcal{N} = 1 bulk orientifold theory in the presence of a D6-brane are analysed by studying the underlying Type IIA supergravity coupled to the brane world volume in the democratic formulation and performing a detailed dualisation procedure. The N=1N=1 \mathcal{N} = 1 chiralcoordinates are found to be in agreement with expectations from mirror symmetry. We work out the Kähler potential for the chiral superfields as well as the gauge kinetic functions for the bulk and the brane gauge multiplets including the kinetic mixing between the two. The scalar potential resulting from the dualisation procedure can be formally interpreted in terms of a superpotential. Finally, the gauging of the Peccei-Quinn shift symmetries of the complex structure multiplets reproduces the D-term potential enforcing the calibration condition for special Lagrangian 3-cycles.
Gesehen am 19.12.2017